SEARCH OF THE MINIMUM OF THE FUNCTIONS WHICH HAVE GAPS OF PARTIAL DERIVATIVES - Yudin, Oleh (Scientific Works of Vinnytsia National Technical University, 2015)
Possible solutions of search of minimum of functions which have partial derivative gap were analyzed. First order method of optimization for solution of the given problem was developed and proved.